Teachers’ Attitudes Towards Inclusive Education: a Cross-National Exploration - Charitaki, G.; Kourti, I.; Gregory, J.L.; Ozturk, M.; Ismail, Z.; Alevriadou, A.; Soulis, S.-G.; Sakici, Ş.; Demirel, C. (Trends in Psychology, 2022)
The study aims to suggest a model for attitudes towards inclusive education that will yield a good fit across different countries. Moreover, we aim to explore the effect of years of teaching experience, educational work level of teachers, and the highest degree completed by teachers on teachers’ attitudes towards inclusion across different countries. A demographic scale and the ATTAS-mm were applied to 908 teachers employed in schools of general education or who offered parallel support and/or resources in five different countries (Greece, the UK, the USA, Malaysia, and Turkey). CFA suggested a 4-factor solution, which included the cognitive, affective, and behavioral factors that have been previously introduced by Gregory and Noto (2012), and a fourth factor, labeled overall attitudes towards teaching all students. In the cognitive factor, the UK had the most positive attitudes. TU, MA, and GR enrolled in the same cluster, and the USA had the least positive attitudes. In the affective factor, GR had the most positive attitude. MA and the USA enrolled in the same cluster and TU and the UK had the least positive attitudes. A similar pattern is observed for the behavioral factor with GR having the most positive attitude. TU and MA enrolled in the same cluster, and the USA and the UK had the least positive attitudes. Finally, years of teaching experience, educational work level, and the highest degree completed have a significant effect on teachers’ attitudes towards inclusion in all countries. Providing feedback for future research is the focal point of the discussion part. © 2022, Associação Brasileira de Psicologia.
Keywords: Affective; Attitudes; Behavioral; Cognitive; Inclusive education; Teachers; dept.edl; peer-reviewed